Monitoring of Lymphocyte Populations During Treatment with Interferon-β-1b to Predict Multiple Sclerosis Disability Progression - Vališ, Martin; Vyšata, Oldřich; Sobíšek, Lukáš; Klímová, Blanka; Andrýs, Ctirad; Vokurková, Doris; Pavelek, Zbyšek (Journal of interferon & cytokine research, 2019)
The authors aim to understand how lymphocyte populations could predict the course of multiple sclerosis (MS) in people treated with interferon-β (IFN-β). Twenty-five male patients and 72 female patients were analyzed in the study. Peripheral blood samples were taken before and 5 years after the treatment with IFN-β. Lymphocyte subsets were analyzed by flow cytometry. The authors compared lymphocyte parameters between confirmed sustained progression (CSP) and non-CSP groups by using Welch's one-way analysis of means or a chi-square test of independence. A penalized (lasso) logistic regression model was fitted to identify the combination of lymphocyte parameters for potential biomarkers. The combination of lymphocyte counts, relative CD3+/CD25+ cells, absolute CD8 T cells, absolute CD8+/CD38+ cells, absolute CD38+ cells, and relative CD5+/CD19+ cells was identified as potential biomarker for the IFN-β treatment to monitor MS development in relation to CSP. The results suggest that other biomarkers aid in patient observation, predict a favorable outcome, and assist in the decision-making process for the early therapy escalation.
Keywords: Humans; Lymphocyte Count; Lymphocytes; lidé středního věku; lymfocyty; interferon beta; Multiple Sclerosis; Interferon-beta; Female; Aged; mladý dospělý; dospělí; senioři; lidé; Adult; ženské pohlaví; roztroušená skleróza; Male; Middle Aged; Young Adult; počet lymfocytů; mužské pohlaví